Developing criteria for evaluations of water closet facilities in Malaysian mosques and it’s compliance with standards, guidelines and legislation - Mohamad Nazir, Amni Umirah; Ramli, Nor Azam; Ismail, Mohd Rodzi; Rasli, Nur Baitul Izati; Shith, Syabiha; Zainordin, Nazatul Syadia (Malay Arts, Culture and Civilization Research Centre, Institute of the Malay World and Civilization, 2018)
Water closets generally provide general facilities, such as wash-hand basins, ablution areas, shower areas and water cubicles (including those for the disabled). This study seeks to developed a list of criteria for evaluation of the design of these ancillary components as defined in various Malaysian standards and guidelines relevant to water closet design, namely, Malaysian Standard MS 2577: 2014 (Architecture and Asset Management of Masjid – Code of Practice), Malaysian Standard MS 2015: Part 1: 2006 (Public Toilet – Part 1: Minimum Design Criteria), Malaysian Standard MS 1184: 2014 (Universal Design and Accessibility in the Built Environment – Code of Practice, Second Revision), JKR 1999 (Guidelines on Buildings Requirements for Disabled Persons) and UBBL: 1984 (Unit Building By-Laws – Part III: Space, Light and Ventilation). A five-point rating scale was developed for the access audit (1=not provided; 2=provided but below the recommendation; 3=provided and exactly as the recommendation; 4=provided but above the recommendation; 5=provided but not in the recommendation). The scores of every criterion were computed to determine the compliance percentage. The study was conducted in five mosques to assess the on-site and as-built compliance of their water closets.